Factors that influence the behaviour of household solid waste management towards zero waste - Md Jusoh, Zuroni; Muhammad Arif, Afida Mastura; Osman, Syuhaily; Mat Salleh, Roslina; A. Kadir, Nurul Aini (Malaysian Consumer and Family Economics Association, 2018)
The study aims to examine the relationship between knowledge, attitude, subjective norms and behaviour of household solid waste management towards zero waste among urban households in eight states in Peninsular Malaysia that have implemented and enforced regulations under the Solid Waste Management and Public Cleansing Act 2007 (Act 672). The study also examines the factors that influence the behaviour of household solid waste management. A total of 605 respondents were involved in this study where they were selected through simple random sampling using quantitative techniques through a questionnaire. Data obtained were analysed using SPSS software. The Pearson Correlation Test is used to examine the relationship between two variables, while Multiple Linear Regression is used to examine the factors that influence the behaviour of household solid waste management. The result shows that knowledge scores are high because the respondents have awareness of the importance of managing household solid waste. Meanwhile, subjective norms score is at a fair level. For attitude and behavioural scores, it was also positive as respondents are involved in solid waste management activities. The findings show that there is a significant relationship between knowledge and behaviour (r = 0.136 **, p = 0.001), a significant relationship between attitude and behaviour (r = 0.175 **, p = 0.000) and also a significant relationship between subjective norms and behaviour (r = 0.472 **, p = 0.000). Multiple Linear Regression analysis also found that knowledge, attitude and subjective norms factors influenced the behaviour of household solid waste management (adjusted R2= .254, F = 69.371 and p <0.01). This shows that the predictor factors ability to explain influencing the behaviour of household solid waste management is as high as 25.4%. In conclusion, knowledge, attitude and subjective norms as predictor variables influence the behaviour of household solid waste management. Therefore, in line with the findings of the study, governments and stakeholders need to play important roles in increasing household knowledge, attitude, subjective norms and behaviour towards household solid waste management among households in the states that have implemented and enforced regulations under the Solid Waste and Public Cleansing Management Act 2007 (Act 672).